CULTURAL AND CIVILIZATIONAL PROCESSES IN EGYPT IN THE XIX CENTURY - Turekulova Zhuldyz (European Scientific Journal, ESJ, 2014)
The article examines the transformations begun in Egypt at the beginning of the XIX century by Muhammad Ali and continued by his successors. It is very important that this stage of the history of Egypt has an extremely wide range of dramatic events of thepoliticalmilitary, socio-economic, cultural and civilizational content. It should also be borne in mind that in that period of history, despite its formal dependence on the Ottoman Empire, Egypt actually turned into one of the leading, largely-independent states in the Middle East.